The Effect Hormone BAP (6-Benzyl Amino Purine) on the Growth of Potato Axillary Shoots (Solanum Tuberosum L.) in Vitro - Dila Lailatul Arafah; Diana Hernawati; Egi Nuryadin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Potatoes are one of the foodstuffs that contain lots of carbohydrates, minerals, and vitamins. To develop potato cultivation, superior varieties are needed that produce high yields, are resistant to pests, and have good tuber quality. The growth of potato plantlets in the in vitro subculture process is determined by many factors, one of which is the administration of growth regulators and the concentration of growth regulators. The type of media or nutrients used also affects the growth and development of the explants and seedlings produced. This study aims to trigger the growth of potato plantlets so that their growth is optimal. The method used is a true experimental quantitative method with a one-factor Completely Randomized Design (CRD) design, namely variations in BAP concentration consisting of 5 treatments with 5 replications. Data collection techniques through observation or observation. Parameters observed were number of shoots, number of leaves, number of roots, and plantlet height. The data analysis technique used is the one way ANOVA test and for the average difference between treatments, the HSD (Honestly Significant Difference) test at 5% level is used. Based on the results of the study, it was known that there was an effect of giving the hormone BAP (6-Benzyl Amino Purine) on the growth of potato axillary shoots (Solanum tuberosum L.) in vitro. The results showed that there was a significant effect on the number of shoots (P = 0.007) with an average of 1.64 pieces, the number of leaves (P = 0.002) with an average of 1.42 pieces, the number of roots (P = 0.000) with an average of 1. an average of 1.70 pieces, and plantlet height (P=0.000) with an average of 2.65 cm. It was concluded that treatment D (1.5 ppm BAP) was the best treatment in increasing the growth of potato plantlets.